Layered Image Encryption Method Based on Combination of Logistic Map, Henon Map, and Sine Map to Enhance Digital Image Security - Amir Musthofa; Moses Setiadi, De Rosal Ignatius (Politeknik Negeri Batam, 2025)
In today's digital era, ensuring the confidentiality of image data is crucial due to the widespread use of images in fields such as medical imaging, military communication, and multimedia applications. This study proposes a layered image encryption method by integrating three chaotic systems: Logistic Map, Henon Map, and Sine Map. Each layer in the encryption process applies a different chaotic map to sequentially perform pixel permutation, XOR-based substitution, and modulus-based substitution. Key generation is carried out by producing pseudo-random number sequences derived from the iterations of each chaotic map: the Logistic Map (using specific initial and control parameters), the Henon Map (with two initial condition variables), and the Sine Map (based on a sine function), all of which are highly sensitive to initial conditions and control parameters. These sequences are then used as keys in each encryption stage. The proposed method strengthens the principles of confusion and diffusion, thereby enhancing the security and randomness of the encrypted images. Evaluation was conducted using metrics such as histogram analysis, entropy, chi-square, correlation coefficient, PSNR, and BER. The experimental results demonstrate that the method produces encrypted images with strong statistical characteristics and high resilience against common cryptographic attacks. Thus, this approach makes a significant contribution to the development of secure and efficient image encryption techniques based on chaos theory.